Evaluation of brackets shear bond strengths using two different light-emitting diode curing units - Ahmad A Abdul-Mawjood (University of Mosul, College of Dentistry, 2006)
Aims: To evaluate the efficiency of two types of light-emitting diode (LED) curing units in bonding orthodontics brackets. Materials and Methods: Three groups, ten teeth each, of newly extracted premolars were used in the study. In the control, the brackets were bonded using a halogen bulb light curing unit, while in the other two groups the brackets were bonded using a high and a low intensity LED curing unit, respectively. The brackets were bonded to the teeth using Transbond® light-cured orthodontic adhesive. The bonded brackets were tested for their shear bond strength using a universal compression machine. Results: The mean bond strength of brackets bonded with the high intensity LED curing unit was above the clinically accepted value and it was comparable to that of the halogen bulb light curing unit group. Meanwhile, the mean bond strength of brackets bonded with the low intensity LED curing unit significantly differed from the other two groups and was below the clinical acceptance level. Conclusion: The high intensity LED curing units can be used successfully in bonding orthodontic brackets. The bond strength was sufficient to consider these units as good substitutes for the halogen bulb-based units. The low intensity LED curing units are not recommended to be used in orthodontics.